Motive of cossack mode of life in the works of Sandzhi Balykov (on the material of the novel “Zalamdzha”) - Nyudlya Chetyrovna, Ochirova (2021)
The article analyzes the motive of the Cossack mode of life in the works of an outstanding representative of Kalmyk literary Diaspora, a publicist, a journalist, a public figure, an officer of the Cossack regiment of the Don army, a participant of the Civil War in Russia, a bearer of living history belonging to the first wave of Russian emigration. As a result of an objective study of definite specific features of the traditional way of life of Don Kalmyks-Cossacks in the works of S.Balykov, the pattern of the writer's appeal to the realities of the traditional Cossack mode of life of Don Kalmyks is examined, the principles of its representation on the material of the novel “Zalamdzha” are revealed, a variety of phenomena related to the the most important concepts  of everyday life, mode of life and foundations of the Don Cossacks-Kalmyks are analyzed. The realities of the national mode of life and the foundations of Kalmyk Cossacks are fully reflected in the writer's works. The consideration of preceding events having made an impact on the writer's works and his interaction with common-literary process gives us reasons to presume the extreme importance of historical cultural phenomena, the reflection of which has become the result of S. Balykov's immediate flashbacks.